HUBUNGAN ANTARA TINGKAT PENDIDIKAN DENGAN KONSEPDIRI PADA WANITA INFERTIL DI RUMAH SAKIT PUTRI SURABAYA - Jaya, Pongki; Manggiasih, Vidia Atika; Andriani, Santi (TALENTA, 2015)
Fertility  is  a  capability of a  wife  to be  pregnant  and  bearing  a live  child  by a husband that able to impregnate her. Infertile woman  is one of case examples with the self-concept  disorder  problem.  Self-concept  disorders  taking  place  may  be  role,  body image,  self-esteem  and  self-identity.  Educational  factor  is  very  important  in  the constructive  coping  uses  in  problem  solving.  From  the  preliminary  survey  at  the  Putri Hospital of Surabaya obtained data that out of 8 infertile women visiting, 50% of them had the low self-concept and otherwise.The  research  methodology  was  conducted  analytically  by  Cross  Sectional approach.  Sample  taking  used  the  saturated  sampling/census,  and  there  was  obtained sample  numbers  as  many  as  30  respondents,  and  filled  in  questionnaire  about  selfconcept. Then data were analyzed by using SPS and t-test.Research  results  indicated  that  out  of  30  infertile  women  respondents  at  the Obstetric  and  Gynecology  In-Patient  Room  of  Putri  Hospital  of  Surabaya  in  2011 indicated  the  existence  of  correlation  between  education  level  and  self-concept.  The higher  the  educational  level  then  also  the  higher  the  self-concept  had.  In  addition,  in general respondent with self-concept that also high. Other support factors such as age, work,  information  and  other  social  factors  likely  can  influence  the  self-concept representation.Knowledge  improvement  via  formal  educational  ladder  generally  needs  to  be improved so that created the better next generation. In the management of infertile cases it also impacted for client in the effective and constructive coping process in coping with problem solving. By understanding self-concept the client had, it is expected can facilitate the assessment process in the KIE delivery conducted both by medical and paramedical staffs psychologically.Key Words: Infertility, Educational Level, and Sel Concept